Pelletization of torrefied palm kernel shell by using different binding agent - Sambeth, Sharwin Kumar; Noor Asma Fazli, Abdul Samad; Suriyati, Saleh (Elsevier Ltd, 2022)
Palm kernel shell (PKS) pellet has huge potential to be used as an energy source due to its physical and chemical properties. Raw palm kernel shell must undergo pretreatment process such as torrefaction to improve its poor qualities such as high moisture content and low energy density. Torrefaction is the thermal treatment which occurs at 200 - 300 ℃ under inert condition. Torrefied biomass is not uniform in size which causes problems in terms of bulk density and storage capacity. To overcome these problems, the pelletization process can be introduced by densification of the torrefied biomass into torrefied pellets. The pelletization process is a complex interaction between forces and biomass particles, which transform loose biomass into pellet form. However, recently the mechanical properties of the pellets have become challenging during transportation and storage since the low durability of pellets can cause a high level of dust, increased fire explosions, and become health hazards to workers. Therefore, this study was conducted to investigate the mechanical durability of torrefied palm kernel shell (PKS) pellet by using four types of binders which were carboxymethylcellulose (CMC), lignin (LIG), starch (STA), and glycerol (GLY). The palm kernel shell was torrefied at 250 ℃ for 30 minutes. After that, the torrefied palm kernel shell was pelletized at 130 ℃ and 12 MPa by using a hot press machine. The torrefied pellet was characterized by maximum comprehensive force, high heating value, density testing, proximate analysis, thermogravimetric analysis (TGA) scanning electron microscopy (SEM), and Fourier-transform spectroscopy (FTIR). The maximum compression force achieved was pellet with carboxymethylcellulose (4448.9 N) continued by lignin, starch, and glycerol with 2279.4 N, 3742.4 N, and 1139.9 N respectively. The result from the high heating value analysis shows the heating value for each pellet with different binders were almost the same (20.6 – 21.3 MJ/kg). However, significant improvement (22.94%) of HHV for torrefied PKS pellet is observed compared to raw PKS. The density of all the pellets was higher than the standard pellet density which is 600kg/m3. Moreover, from the proximate analysis the ash content of CMC, LIG, STA pellets have less than 5% except the GLY and STA pellets. The FTIR analysis shows changes in chemical bonds between different pellets. From the SEM analysis, it clearly shows pellet with carboxymethylcellulose as a binder have less void and spaces between particles which give positive effect to compression force. TGA analysis also shows differences in terms of ignition, peak, and burnout temperature when different binders were added to torrefied PKS. In conclusion, carboxymethylcellulose can be used as a binder which gives the highest mechanical durability, low ash content, improved HHV for torrefied palm kernel shells to be used as biofuel pellets for heat and power generation.